PIDANA MATI SEBAGAI ULTIMUM REMEDIUM TERHADAP PELAKU TINDAK PIDANA KORUPSI DANA BANTUAN SOSIAL COVID-19 (Solusi, 2023)
Law no. 31 of 1999 in conjunction with Law no. 20 of 2001 confirms the rules regarding the death penalty in Article 2 paragraph (2), namely "In the event that the criminal act of corruption as intended in paragraph (1) is committed under certain circumstances, the death penalty can be imposed." Thus, if you look at the phrase "certain circumstances" in Article 2 paragraph (2), it is interpreted as circumstances that can be used as a reason for criminal aggravation for perpetrators of criminal acts of corruption, such as overcoming dangerous situations, national natural disasters, overcoming the consequences of widespread social unrest, overcoming the economic and monetary crisis. So it can be said that the criminal act of corruption in Covid-19 social assistance funds is included in certain circumstances, so that perpetrators of the criminal act of corruption in Covid-19 social assistance funds can be subject to the death penalty as regulated in Article 2 paragraph (2). The death penalty is the ultimum remedy for perpetrators of criminal acts of corruption which is only carried out if other efforts are unable to overcome the criminal act of corruption.